Modernization of financial incentives to increase the efficiency of the economy of Kazakhstan - Alieva , Amangeldі, B., B. M., B. (Journal of Economic Research & Business Administration, 2016)
The current stage of development of Kazakhstan’s economy is characterized by the analysis and interpretation of the causes and results of the global crisis and global trends in the world ekonomiki.Teoretichesky analysis of economic development in the developed countries of the West and Southeast Asia after World War II showed that only those countries that have made a big «breakthrough» in its economic development, the strategy chosen is not «catch-up» and the strategy to accelerate the introduction of new and modern equipment and technology, innovation in strategically important sectors, which provided them with accelerated development, gained as a result of the key positions in the world market. In line with the implementation of these tasks is very important modernization of financial incentives to increase the efficiency of the economy Kazahstana. V Therefore, in this article reveals four special stages of national economic competitiveness, corresponding to the four major driving forces or stimuli, defining its development in individual periods analyzed three options industrialization objectives and state program of modernization of the economy. Also in this paper we consider the experience of foreign countries to study and use of the principles and methods of economic modernization, offers advice on selecting options modernize the economy and its transition to an innovative path of development.